#### Answer

f(x) = x + 1
g(x) = 2x
fog(x) = 2x +1
gof(x) = 2(x + 1)

#### Work Step by Step

f(x) = (x + 1)
g(x) = (x $\times$ 2) = 2x
fog(x) = f(g(x)) = f(2x) = 2x + 1
gof(x) = g(f(x)) = g(x+1) = 2(x + 1)

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

f(x) = x + 1
g(x) = 2x
fog(x) = 2x +1
gof(x) = 2(x + 1)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.